Attitude of small-scale fishermen towards adaptation to climate change - Muhammad, Mahazan; Idris, Khairuddin; Mohamed Shaffril, Hayrol Azril; Sulaiman, Abdul Hadi; Abu Samah, Bahaman; Suandi, Turiman (Universiti Putra Malaysia Press, 2018)
It is globally accepted that the earth's climate is changing. Such a phenomenon affects communities across the globe. One of these communities is that of small-scale fishermen. Past studies have shown poor understanding of climate change and low progress in development among fishermen because of the failure among stakeholders in understanding the mindset of beneficiaries such as their attitudinal setting. Much of the top-to-bottom development is impromptu, and most of the time, this makes them disorientated and may open them to the risks associated with climate change. Therefore, a better understanding of their attitude in relation to climate change will provide an important foundation for future planning for climate change mitigation and engagement of fishermen communities with stakeholders. In general, this paper aims to determine the attitude of small-scale fishermen towards adaptation to climate change. The nature of this study is quantitative and the study uses a set of questionnaires and involves a total of 300 respondents from two fisheries districts in Peninsular Malaysia. The fishermen surveyed had a high level of adaptation with regards to attitude towards climate change, while their level of education, catching area, fishing technology, type of vessel and income are confirmed as influential factors.